Potentials of Organic Agriculture in Nepal - Bhatta, Gopal Datt; Doppler, Werner; KC, Krishna Bahadur (Journal of Agriculture and Environment, 2009)
Increasing use of agro-chemicals, higher production cost and deteriorating ecosystem health have advocated the need to change traditional and external input use agriculture towards safe and sustainable organic production. Current research focuses on the constraints and opportunities of organic agriculture and consumers' awareness and willingness to pay more for organic vegetables by selecting producers from Lalitpur and Bhaktpur districts using spatial sampling and consumers from Kathmandu valley randomly. Data obtained from structured questionnaire were subjected to descriptive and econometric analysis and willingness to pay analysis. Most of the farmers interviewed are aware about the negative repercussion of the indiscriminate use of agro-chemicals. Organic vegetables are either home delivered and/or sold to the specialized niche markets. All domestic organic products reach to consumers without labeling. Most of the organic consumers are willing to pay eight rupees more for labeled organic vegetables. Currently organic farmers rely only on consumers' willingness to pay more to obtain a compensation for lower yields. Family income, education, profession etc are key attributes of the consumers shaping their decision to buy organic vegetables. Organic industry is too small and a long way to go in Nepal. Political commitments such as avoiding conflicting drive to maximize production, hammering proactive policy, initiating organic technology research, providing market incentives and institutionalization of Nepalese organic movement are imperative to further enhance organic sector in Nepal. Key words: Awareness; Consumers; Marketing; Organic vegetables; Regression; Willingness to pay The Journal of Agriculture and Environment Vol:10, Jun.2009 Page: 14